Outcomes of peritonitis among patients with peritoneal dialysis: a comparison between culture-positive and culture-negative peritonitis - Watcharotone, Narongsak; Moungson, Wasana; Luekhamhan, Thunyluck; Banlusook, Rungnapa; Pansaksiri, Somsiri (Journal of the Nephrology Society of Thailand, 2022)
Background: Peritoneal dialysis-related peritonitis increased risks of morbidity and mortality among patients undergoing peritoneal dialysis. The treatment decision depended on results of dialysate fluid culture but in culturenegative peritonitis, antibiotics covering both gram positive and negative bacteria were selected. This study aimed to analyze results of peritonitis treatment among patients undergoing peritoneal dialysis of our center. Methods: This retrospective study collected all files of patients undergoing peritoneal dialysis in Saraburi Hospital presenting peritonitis from January 2008 until December 2019 and analyzed treatment outcomes between culture - positive and culture-negative groups. Results: Two hundred seventy-eight patients completed the study. Of those 50.7% were men, patients’ age, diabetes, and hypertension were 52.93±14.91 years, 54.32%, and 33.81%, respectively. Peritonitis events totaled 1.76±1.03 per person of which 21.59% involved negative culture. Staphylococcus species, E. coli and Streptococcus species were common organisms in culture-positive peritonitis (28.83, 15.32, and 13.25%, respectively). No different outcomes were found between culture-positive and culture-negative peritonitis groups in duration of antibiotic administration, refractory peritonitis, catheter removal, and catheter re-insertion (10.38±10.50 days vs. 12.04±9.00 days, p = 0.138, 35.06 vs. 34.90%, p = 0.98, 31.95 vs. 29.24%, P=0.59, and 22.76 vs. 19.35%, P= 0.68, respectively). From all cases, 36.69% were changed to hemodialysis. No difference was observed in mortality between culture-positive and culture-negative peritonitis groups (P=0.093). Conclusion: In the present study, even though we found no difference in outcomes between culture-positive and culture-negative peritonitis among patients with PD, it still constituted a major cause of catheter removal and change of dialysis modality.